2012
DOI: 10.1007/s10162-012-0331-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Suppression of Tinnitus by Modulated Sounds

Abstract: Despite high prevalence of tinnitus and its impact on quality life, there is no cure for tinnitus at present. Here, we report an effective means to temporarily suppress tinnitus by amplitude- and frequency-modulated tones. We systematically explored the interaction between subjective tinnitus and 17 external sounds in 20 chronic tinnitus sufferers. The external sounds included traditionally used unmodulated stimuli such as pure tones and white noise and dynamically modulated stimuli known to produce sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 63 publications
8
64
1
4
Order By: Relevance
“…For some of these emerging sound treatments (eg, acoustic coordinated reset neuromodulation, sere nade, and frequency discrimination training), the sug gested target site of action is the central auditory system, with the sound individually tailored to the hearing loss and tinnitus characteristics to interrupt the maladaptive neuroplasticity driving the tinnitus sensation. 51,52 Other interventions use sound mostly as a therapeutic relaxant (eg, Widex Zen 53 ), while the Neuromonics device is said to reduce emotional arousal, and target the eff ects of auditory deprivation through spectrally shaped sound. 54 Typically, the commercial devices are recommended as part of a holistic audiological management programme that incorporates education and counselling.…”
Section: Emerging Sound Treatmentsmentioning
confidence: 99%
“…For some of these emerging sound treatments (eg, acoustic coordinated reset neuromodulation, sere nade, and frequency discrimination training), the sug gested target site of action is the central auditory system, with the sound individually tailored to the hearing loss and tinnitus characteristics to interrupt the maladaptive neuroplasticity driving the tinnitus sensation. 51,52 Other interventions use sound mostly as a therapeutic relaxant (eg, Widex Zen 53 ), while the Neuromonics device is said to reduce emotional arousal, and target the eff ects of auditory deprivation through spectrally shaped sound. 54 Typically, the commercial devices are recommended as part of a holistic audiological management programme that incorporates education and counselling.…”
Section: Emerging Sound Treatmentsmentioning
confidence: 99%
“…Acoustic sound enrichment by either conventional hearing aids [Saltzman and Ersner, 1947;Shekhawat et al, 2013;Hoare et al, 2014], tinnitus maskers [Erlandsson et al, 1987;Vernon and Meikle, 2003;Fioretti et al, 2012] or music with tinnitus-related modification [Davis et al, 2007;Pantev et al, 2012a, b;Reavis et al, 2012;Tass et al, 2012] is a potential treatment option but shows a large variability in effectiveness among patients. This variability may be explained by the heterogeneity of tinnitus, which is caused by auditory deprivation and can occur at various positions along the auditory pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[50] Compatible with this idea, a case study exploring protocols of acoustic stimulation reported how a 6-kHz tone amplitude-modulated at a rate of 40 Hz was judged to provide tinnitus suppression. [47] More recently, Reavis et al, [51] examined the short-term suppressive effects of external sounds (17 modulated sounds at different modulation rates and carrier frequencies, and un-modulated sounds at different carrier frequencies) matched to the tinnitus loudness. They found that the greatest immediate suppression was induced by 40-Hz amplitude-modulated tones with carrier frequencies near the tinnitus pitch.…”
Section: Evaluation Of Its Efficacy and Neurophysiological Mechanism mentioning
confidence: 99%